Progressive Islamic Educational Management and Human Resource Sustainability in Islamic Schools - Karim, Abdul; Fakhruddin, Agus; Jenuri, Jenuri; Budiyanti, Nurti; Sianturi, Risbon; Kulkarni, Shirin (Jurnal Pendidikan Islam, 2025)
Sustainable human resource development has become a critical issue in Islamic educational institutions as they respond to changing educational demands while preserving Islamic values. This scrutinizes how progressive Islamic Educational Management (IEM) practices contribute to the sustainability of human resources in two Indonesian Islamic schools. Employing a qualitative-dominant mixed-method design, data were collected through in-depth interviews, structured observations, document analysis, and a brief descriptive survey involving 32 educators and administrative staff. The findings reveal that both institutions implement progressive management strategies that emphasize adaptation, innovation, and continuous professional development grounded in Islamic principles. The Islamic elementary school demonstrates a strong integration of spiritual development and managerial professionalism, while Islamic Junior high school highlights institutional adaptability and active community engagement. Furthermore, the study shows that visionary leadership, human-centered policies, and reflective evaluation mechanisms play a central role in sustaining the quality and commitment of educational personnel. These results contribute to a deeper understanding of IEM as a framework for sustainable leadership and organizational development within Islamic schools. This study implies that Islamic educational institutions can strengthen long-term human resource sustainability by harmonizing Islamic values, progressive management practices, and professional well-being.